2022
DOI: 10.1016/j.japh.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

A coordinated strategy to develop and distribute infographics addressing COVID-19 vaccine hesitancy and misinformation

Abstract: Background: Visual communication strategies are becoming increasingly prevalent for conveying information to health professionals as well as to the general public. The potential of social media for rapid knowledge dissemination using infographics was recognized early in the coronavirus disease (COVID-19) pandemic by health professionals. Objective: The purpose of this study was to describe a coalition of health professionals' approach to developing infographics about COVID-19 vaccines and the reach and engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Of the 45 included studies, 18 (40%) studies reported misinformation across all 3 categories [ 27 - 29 , 35 - 37 , 45 , 48 , 49 , 51 , 55 , 57 , 58 , 60 - 62 , 67 , 68 ], 9 (20%) studies reported only on conspiracies [ 26 , 30 , 33 , 42 , 44 , 46 , 53 , 54 , 56 ], 6 (13%) studies were concerned specifically with medical misinformation [ 25 , 34 , 38 , 43 , 63 , 64 ], and 12 (27%) studies reported on COVID-19 vaccine misinformation or antivaccine discourse without going into further detail [ 31 , 35 , 39 - 41 , 47 , 52 , 59 , 65 , 66 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 45 included studies, 18 (40%) studies reported misinformation across all 3 categories [ 27 - 29 , 35 - 37 , 45 , 48 , 49 , 51 , 55 , 57 , 58 , 60 - 62 , 67 , 68 ], 9 (20%) studies reported only on conspiracies [ 26 , 30 , 33 , 42 , 44 , 46 , 53 , 54 , 56 ], 6 (13%) studies were concerned specifically with medical misinformation [ 25 , 34 , 38 , 43 , 63 , 64 ], and 12 (27%) studies reported on COVID-19 vaccine misinformation or antivaccine discourse without going into further detail [ 31 , 35 , 39 - 41 , 47 , 52 , 59 , 65 , 66 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 19 studies that made assumptions regarding the effects of social media misinformation on vaccine hesitancy ( Table 3 ). The evaluation of the certainty of evidence of these 19 studies that measured the “Association between social media misinformation and COVID-19 vaccine hesitancy” was classified as moderate or low to moderate according to GRADE in 2 cases [ 38 , 65 ]. For the rest of the studies, the certainty of evidence according to GRADE was considered low or very low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, within the IMPACT amplifier, a member might share a piece of disinformation that they feel could be better addressed with more nuance in an infographic or a video. This can then be escalated to the team within the coalition developing Myth Buster infographics [ 23 ], following the Fact, Myth, Fallacy, Fact refutation strategy for combating misinformation, popularized by climate change activists and described in The Debunking Handbook [ 24 ]. Other groups such as No License For Disinformation use their own amplifier to facilitate group discussion, identify misinformation, and alert the public and platforms that content is incorrect [ 25 ].…”
Section: Combating Misinformation and Disinformationmentioning
confidence: 99%
“…Interestingly, our partner organization IMPACT4HC adopted a geography-first approach to fighting the infodemic, bringing together a coalition of Chicago-based health care providers, and have found that their place-based infodemic management efforts have yielded appreciable online spillovers. 11 …”
Section: Let’s Learnmentioning
confidence: 99%